Efecto de la densidad de siembra sobre el crecimiento y supervivencia de anadara tuberculosa (sowerby, 1833) con semillas obtenidas en laboratorio - Mendoza Neyra, Oscar Augusto (2013)
ABSTRACT The present research was carried out in the adjacent mangroves to the Faculty of Fishing Engineering of the National University of Tumbes (3°30'21,43" S and 80°23'48,36" W), from January 25th of 2012 to January 26th of 2013, the general objective was to determine the effect of the sowing density on the increment in length and weight, as well as the survival of Anadara tuberculosa sowed in its natural environment, the swamp, to three densities with seeds obtained in laboratory. To achieve the purpose, corrals of 2m x 1m where settled, there were three treatments t1=20, t0=40, and t2=60 (ind./m-2), during twelve months. During the investigation the total length of the valve was measured (lt), height of the valve (h), thickness of the valve, all in millimetrer and the total weight (pt) in grams. During the first five months the increment in length as well as in weight was smaller (0,98±0,68 mm/month and 0,15±0,09 g/month) that in the seven successive months (1,4±0,37 mm/month and 0,27±0,09 g/month); however, although statistically through an Analysis of Variance to a level of 95% of confidence, there was no significant difference among them, the treatment t1 (20 ind./m-2) had the highest increment in length and weight (1,36±0,47 mm/month and 0,26±0,12 g/month) than the others t0 and t2 (0,95±0,68 and 0,94±0,64 mm/month; 0,22±0,14 and 0,22±0,14 g/month). The survival was higher in the treatment t1 (20 ind./m-2) with 60,7% that in the treatments t0 andt2 (50,58% and 49,56%).